Molecular Pathology, Diagnostics, and Therapeutics of Nephropathy - Kronbichler, Andreas; Tesar, Vladimir (International journal of molecular sciences, 2022)
Years of standing still have ended, and the field of nephrology has seen a plethora of clinical trials, changing the therapeutic landscape of chronic kidney disease (CKD) and immune-mediated kidney disease management [...].
Keywords: ledviny; nefrologie; Kidney; Humans; lidé; Renal Insufficiency, Chronic; chronická renální insuficience; Pathology, Molecular; Nephrology; molekulární patologie